2014
DOI: 10.1039/c4nr00300d
|View full text |Cite
|
Sign up to set email alerts
|

Coiled fiber scaffolds embedded with gold nanoparticles improve the performance of engineered cardiac tissues

Abstract: Coiled perimysial fibers within the heart muscle provide it with the ability to contract and relax efficiently. Here, we report on a new nanocomposite scaffold for cardiac tissue engineering, integrating coiled electrospun fibers with gold nanoparticles. Cultivation of cardiac cells within the hybrid scaffolds promoted cell organization into elongated and aligned tissues generating a strong contraction force, high contraction rate and low excitation threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
102
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 27 publications
4
102
0
Order By: Relevance
“…Electrospinning is a well-established method used in tissue engineering to fabricate fibrous scaffolds (9,10,(22)(23)(24). We have recently reported on the potential of albumin fiber scaffolds to promote the assembly of anisotropic and functional cardiac patches.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrospinning is a well-established method used in tissue engineering to fabricate fibrous scaffolds (9,10,(22)(23)(24). We have recently reported on the potential of albumin fiber scaffolds to promote the assembly of anisotropic and functional cardiac patches.…”
mentioning
confidence: 99%
“…Numerous approaches have been used to recapitulate different structural properties of the heart (7)(8)(9)(10)(11). Technologies such as lithography and microfabrication enabled precise control over the biomaterial pattern and thus over the induced cell alignment and anisotropic electrical signal transfer (8,12).…”
mentioning
confidence: 99%
“…For example, gold nanowires were incorporated into porous alginate scaffolds to improve scaffold conductivity for cardiac cell culture (81). To mimic the coiled fibers of the native heart matrix as well as high electrical conductivity, neonatal rat CMs were cultivated on scaffolds generated from electrospun poly(ε-caprolactone) micro-fibers doped with gold nanoparticles (82). Tough, yet flexible scaffolds with enhanced electrical properties were created by incorporating carbon nanotubes (CNTs) into aligned poly(glycerol sebacate):gelatin electrospun nanofibers (83).…”
Section: Tissue Engineering and Biomaterials For The Restoration Omentioning
confidence: 99%
“…The incorporation of gold nanoparticles (AuNPs) is another conductive substance that is used to improve conductivity and mechanical properties. Fleischer et al added AuNPs to PCL and reported that this addition of AuNPs affected the morphology of the cardiac tissues [136]. The morphology of the cells was elongated and aligned, which mimics the morphology inside the myocardium.…”
Section: Co-electrospinning With Conductive Materialsmentioning
confidence: 99%